A self-perception of ageism among elderly individuals during the covid-19 pandemic - Santoro, Marcia Batista (2025)
The objective of the study was to analyze the self-perception of elderly individuals regarding ageism during the COVID-19 pandemic in the Amazonas state. A quantitative and qualitative study was conducted in Manaus, AM, with a sample population of 44 elderly individuals aged ≥ 60 years, of both sexes, who were affected by the COVID-19 pandemic from March 2020 to May 2023. The study was divided into two stages. The first stage consisted of a quantitative study, of the observational epidemiological type, cross-sectional, in which information was collected through the application of a Likert-type ageism self-perception scale. The second stage consisted of a qualitative study composed of two open-ended questions related to experiences of ageism during the COVID-19 pandemic by the research participants, who were interviewed in structured interviews, with 10 volunteers in total, representing a percentage of 20% of the participants. The results showed that 75% of the respondents experienced two or more situations of ageism. They self-reported two or more types of ageism compared to those who did not report ageism or reported only one type of ageism. In the qualitative analysis, mesostructural and macrostructural ageism, predominantly of explicit origin, were observed. We concluded that the COVID-19 pandemic increased instances of ageism experienced by elderly individuals in Manaus, particularly noting that this discrimination occurred among healthcare professionals and public transportation drivers. We acknowledge the study's sample size limitation and its focus on a specific elderly population. However, it is extremely important to establish strategies to combat ageism through strengthening and updating policies and laws, as well as educational and research interventions.